Prevention of mother-to-child transmission of hepatitis B virus and hepatitis C virus. Issue 7 (July 2014) - Gentile, Ivan; Zappulo, Emanuela; Buonomo, Antonio Riccardo; Borgia, Guglielmo
Abstract : About 240 million people worldwide are chronically infected with hepatitis B virus (HBV). Vertical transmission is the most important mechanism of infection persistence in endemic areas. About 150 million people worldwide are chronically infected with hepatitis C virus (HCV). Mother-to-child transmission of HCV, which occurs in 3–10% of cases, is the leading route of infection in childhood. This review focuses on strategies to reduce the vertical transmission of HBV and HCV. The at-birth prophylaxis of newborns of HBV-infected mothers with specific immunoglobulin and vaccine plus administration of antivirals (tenofovir or telbivudine) in the third trimester of pregnancy (in case of high maternal viral load) greatly reduces the risk of transmission. In contrast, currently there is no drug able to reduce the vertical transmission of HCV infection. We discuss the possibility of reducing mother-to-child HCV transmission using newly available antivirals or antivirals in the pipeline for the treatment of hepatitis C.